KAIDAH KUALIFIKASI INTELEKTUAL MUFASSIR: Abdul Basid, Prodi Ilmu al-Qur’an dan Tafsir IAI Bani Fattah Jombang - Abdul Basid (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2018)
This article focuses on some intellectual requirements of Koran interpreters and their urgency and effect to the Koran interpretation. the article argues that interpreting Koran requires some disciplines of knowledge one must master them before interpreting the Koran. It also gives us proves of the urgency of the some disciplines of knowledge effects the quality of the interpretations. This article specially will presentation in the tafsir Hadith class.